Successful treatment with low‐dose oral steroids for contracted bladder after intravesical instillation of Bacillus Calmette–Guérin - Akinobu Katami; Takamitsu Inoue; Hiromichi Sakurai; Mizuki Onozawa; Shin‐ichi Hisasue; Koji Kawai; Jun Miyazaki (IJU Case Reports, 2024)
Introduction Contracted bladder is a rare adverse effect of intravesical Bacillus Calmette–Guérin instillation, with an incidence of 0.2–3.3%. This report aimed to present a case of contracted bladder successfully treated with a low‐dose oral steroid. Case presentation A 78‐year‐old man underwent a third transurethral resection of a bladder tumor. The pathological diagnosis was urothelial carcinoma in situ. After the fifth instillation of the second‐line induction therapy of Bacillus Calmette–Guérin, the patient discontinued treatment because of increased urinary frequency and a continuous mean voiding volume of 80 mL. The patient was diagnosed with a contracted bladder based on computed tomography findings and a urination chart. After initiating oral prednisolone (20 mg/day), the patient experienced significant recovery within 2 weeks for both urinary frequency and mean voiding volume of 226 mL. Conclusion A patient with a contracted bladder after Bacillus Calmette–Guérin instillation was successfully treated with low‐dose oral steroid therapy.